Un incontro al Salone del libro di Torino - Vari, Autori (Il sogno della farfalla, 2010)
After having presented his book Fantasia di sparizione. Lezioni 2007 at the University of Chieti, which this magazine then featured in Issue 3, 2009, another encounter for the same book is now being proposed which took place on 16.5.2009 in the particular context of the Salone del Libro di Torino. The book’s contents (starting with the reproposal of the discovery of the disappearance fantasy), its story and epistemological, cultural and political implications, as well as a number of aspects of its production are some of the themes raised by the speakers in their talks (the publisher Matteo Fago, the historian David Armando, the physicist Marco Pettini and the philosopher Giacomo Marramao) and in the short debate where the author took part as well.